High-performance large-area WS2-based transistors by a novel tin-oxide assisted liquid-phase exfoliation: doping adjustment by plasma treatment. (15th January 2021) - Esfandiari, Mehrnaz; Kamaei, Sadegh; Rajabali, Mona; Mohajerzadeh, Shamosddin
Abstract: We report a novel strategy to stitch small WS2 flakes to form larger features in liquid-phase exfoliation. Owing to the initial granular size of the bulk WS2, which, is around 2 µ m, the use of conventional liquid-based exfoliation techniques leads to small area nanoflakes with sizes around 1 μ m. However, by joining smaller flakes through tin-oxide quantum dot (SnO2 QD) decoration during probe sonication, sheets up to 20 μ m are achieved. The neighboring flakes could stitch together to form larger features through the Sn–S and Sn–O bonds at their lateral sides of their flakes and to realize mosaic arrangement of arbitrary shaped larger sheets. While the original WS2 flakes show n-type behavior, an interesting conversion into a p-channel behavior is observed upon addition of SnO2 QDs followed by additional SF6 plasma treatment process. Additionally, we have investigated the use of SF6 plasma treatment to enhance the carrier mobility and on-off ratio of the field effect transistors, yielding an effective field-effect-mobility of 80 cm 2 V −1 s −1 and relatively high on/off current ratio of 10 5, indicating its superior electronic properties.